Noble guests in organic cages–encapsulation of noble gases by cryptophane - Ćoćić, Dušan; Puchta, Ralph; van Eldik, Rudi (Journal of Coordination Chemistry, 2020)
With the application of DFT calculations (ωB97XD/def2-SVP/SVPfit), the ability and mechanism of noble gas encapsulation by cryptophane was investigated. Based on the applied model reaction, by monitoring geometric changes and investigating the non-covalent interactions between the studied hosts and the noble gases, the size of the host did not necessarily play a decisive role in the selective encapsulation of the guests. Rather the adjustment of the host’s interior and functionalization of its “gates” can be significant in tuning the affinity of cryptophanes.
CRIS-Team Scopus Importer:2020-10-02
Keywords: cryptophane; DFT; host-guest chemistry; Noble gases